The Relationship between Financial Distress and Financial Health Prediction Model: A Study in Public Manufacturing Companies Listed on Indonesia Stock Exchange (IDX) - Khaira Amalia Fachrudin (Jurnal Akuntansi dan Keuangan, 2020)
Financial distress prediction models of Altman, Springate, Zmijewski, Grover, and Khaira have been widely applied to predict financial distress and financial health. This study aims to analyze score correlations within the prediction results of the mentioned models applied in manufacture companies listed in the Indonesian Stock Exchange. The sample includes 30 companies which faced financial distress during economic crisis in 1997–1998 and, as comparison, incorporates 28 financially healthy companies. Observations were made during one and two years before the financial distress occurred, i.e. between 1995 until 1999, as well as from 2015 until 2018 to measure the financial health level in the companies. In this study, we use the correlation analysis. The results showed that  models which have a strong and significant relationship at alpha 5% are models from Altman - Springate, Altman - Khaira, Springate - Khaira, and Zmijewski - Khaira. Grover model which does not have the predictor in the form of leverage, however has a weak correlation with other model as well as the actual condition